2020
DOI: 10.1002/chem.201905083
|View full text |Cite
|
Sign up to set email alerts
|

Boron‐Containing Lipids and Liposomes: New Conjugates of Cholesterol with Polyhedral Boron Hydrides

Abstract: As eries of boron-containing lipids werep repared by reactions of cyclic oxonium derivatives of polyhedron boranesa nd metallacarboranes (closo-dodecaborate anion, cobalt and iron bis(dicarbollides)) with amine and carboxylic acids which are derived from cholesterol. Stable liposomal formulations,o nt he basis of synthesized boron-containing lipids, hydrogenated soybean l-a-phosphatidylcholinea nd (HSPC) 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-2000] (DSPE-PEG) as excipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 92 publications
(108 reference statements)
0
32
0
1
Order By: Relevance
“…Recently, Bregadze et al (2020) reported cholesterol derivatives of closo-dodecaborane, cobalt and iron bis(dicarbollide), which form liposomes together with hydrogenated (Soy) L-α-phosphatidylcholine (HSPC) and 1,2-distearoylsn-glycero-3-phosphoethanol-amine-N-[methoxy(polyethylene glycol)-2000] (DSPE-PEG). [119] DLS and TEM experiments were performed to identify the size distribution of the new liposomes and the lipid bilayer structure. One sample with different sizes was presented, however, without showing the size distribution from TEM experiments; unfortunately, no detailed information was given on the DLS measurements.…”
Section: Liposomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Bregadze et al (2020) reported cholesterol derivatives of closo-dodecaborane, cobalt and iron bis(dicarbollide), which form liposomes together with hydrogenated (Soy) L-α-phosphatidylcholine (HSPC) and 1,2-distearoylsn-glycero-3-phosphoethanol-amine-N-[methoxy(polyethylene glycol)-2000] (DSPE-PEG). [119] DLS and TEM experiments were performed to identify the size distribution of the new liposomes and the lipid bilayer structure. One sample with different sizes was presented, however, without showing the size distribution from TEM experiments; unfortunately, no detailed information was given on the DLS measurements.…”
Section: Liposomesmentioning
confidence: 99%
“…The boron medicinal chemistry literature is rich of examples of elaborated and well-established synthetic approaches to boron-loaded NP platforms and biological macrovectors, [108][109][110]112,113,138,150,175,176] which are accompanied by experiments to determine the loading efficiency and investigate drug release kinetics, at least as preliminary evaluation under simulated biological conditions, especially in the latest works. [107,119,149,177,178] Loading efficiency is generally investigated using a combination of LS techniques (SLS, DLS), calorimetry (mostly, ITC) and 1 H NMR spectroscopy, particularly in the case of (co)polymeric matrices as carrier systems (Figure 9). [110][111][112][113]116] These techniques can give direct access to nano-object formation mechanisms, preferential binding sites and motifs, which indirectly give (semi-)quantitative information on, for example, maximum loading capacity and/or loading-carrier ratios, often expressed as segment/probe ratios (see, e. g., ref.…”
Section: Chemical Stability: Drug Loading and Leakagementioning
confidence: 99%
See 3 more Smart Citations